Komunitas Mikrob pada Hasil Fermentasi Nata De Coco Berdasarkan Marka Random Amplified Polymorphic DNA - Raden Ajie Syahbarie; Antonius Suwanto; Aris Tri Wahyudi (Jurnal Ilmu Pertanian Indonesia, 2023)
Traditional nata de coco fermentation often results in inconsistent nata thickness. From the producer's perspective, thin nata sheets are detrimental because most fermentation media will be wasted. The main cause of this condition may be that the microbial population in the starter culture is different in each batch. It is necessary to observe the cultured microbial community on various qualities of available thick and thin nata to design a better nata de coco starter culture. This study showed thick nata had more Komagataeibacter intermedius bacteria (pellicle forming) than thin nata. In traditional nata fermentation, K. intermedius always coexists with other microbes from the bacteria and yeast groups. Random Amplified Polymorphic DNA (RAPD) analysis indicated that the genetic diversity of bacteria was higher than that of the yeast group. Keywords: dendrogram of relationship, fermented food, microbial genetic diversity, nata de coco